2013
DOI: 10.1371/journal.ppat.1003256
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Triggers RIG-I/TLR3/NLRP3-dependent Inflammasome Activation in Influenza A Virus Infected Cells

Abstract: Influenza A virus (IAV) triggers a contagious and potentially lethal respiratory disease. A protective IL-1β response is mediated by innate receptors in macrophages and lung epithelial cells. NLRP3 is crucial in macrophages; however, which sensors elicit IL-1β secretion in lung epithelial cells remains undetermined. Here, we describe for the first time the relative roles of the host innate receptors RIG-I (DDX58), TLR3, and NLRP3 in the IL-1β response to IAV in primary lung epithelial cells. To activate IL-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
235
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(244 citation statements)
references
References 43 publications
6
235
2
1
Order By: Relevance
“…8), in which AIM2-deficient AMs fail to produce IL-1b in response to IAV infection. Although in vitro inflammasome studies have shown that influenza infection can activate inflammasome in respiratory epithelial cells (23,49,50) and immune cells (51)(52)(53), our results reveal a central role for AMs in AIM2-related inflammasome regulation.…”
Section: Ams Are the Likely Target Cells For Aim2 Function In Regulatcontrasting
confidence: 54%
See 2 more Smart Citations
“…8), in which AIM2-deficient AMs fail to produce IL-1b in response to IAV infection. Although in vitro inflammasome studies have shown that influenza infection can activate inflammasome in respiratory epithelial cells (23,49,50) and immune cells (51)(52)(53), our results reveal a central role for AMs in AIM2-related inflammasome regulation.…”
Section: Ams Are the Likely Target Cells For Aim2 Function In Regulatcontrasting
confidence: 54%
“…7 show that AIM2-deficient mice display steadily improved survival compared with WT mice after different doses and strains of IAV challenge. The survival rate in AIM2 2/2 mice doubled with the low dose of infection (0.5LD 50 ) and increased to 6-fold with the high dose of PR8 infection (50LD 50 ) at the end of observation (Fig. 7A).…”
Section: /2mentioning
confidence: 95%
See 1 more Smart Citation
“…Fascinatingly, these findings suggest the existence of dual roles for RIG-1 in the inflammasome and type 1 IFN pathways. A more recent study on primary human bronchial epithelial cells infected with influenza showed RIG-I-dependent priming of the NLRP3 inflammasome as well as direct RIG-I-mediated inflammasome activation [4]. Therefore, it can be assumed that RIG-I could activate its own inflammasome in response to some viruses, but its major functions in RIG-I-MAVS signalling and NLRP3 inflammasome activation are still the subject of debate, and further research is vitally needed.…”
Section: Rig-1mentioning
confidence: 99%
“…This CARD-CARD interaction results in the dimerisation of MAVS in the mitochondria to form a protein complex called the MAVS signalosome, which enables the activation of NF-jB and the production of type I interferon (IFN). Once the innate immune system has been activated, it elicits the secretion of cytokines and chemokines, which subsequently induce the expression of adhesion molecules and costimulatory molecules to further activate the adaptive immune response [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%